Mortality of lung cancer as a second primary malignancy: A population‐based cohort study - Deng, Lei (Cancer Med, 2019)
Lung cancer as a second primary malignancy (lung‐2) is increasingly common, but its prognosis is poorly understood. This study aims to examine the overall and cancer‐specific survival of patients diagnosed with lung‐2 compared to lung‐1. Primary lung cancer patients diagnosed from 1988 to 2014 in the Surveillance, Epidemiology, and End Results (SEER) program were included. Lung‐2 was identified in patients with a previous diagnosis of nonlung primary malignancy in SEER. Hazard ratios (HRs) of overall and lung cancer‐specific mortality were estimated among patients with lung‐2 compared to lung‐1, adjusting for age and calendar period at diagnosis, sex, race, socioeconomic status, tumor stage, histology, tumor grade, and treatment. A total of 679 541 and 85 758 patients were identified as lung‐1 and lung‐2, respectively. Compared to lung‐1, patients with lung‐2 were more likely to be diagnosed at localized stage, with smaller primary tumor, and treated with surgery. Lung‐2 patients were at lower risk of lung cancer‐specific mortality in the first 5 years (HR, 0.77; 95% CI, 0.76‐0.78 at <1 year; HR, 0.87; 95% CI, 0.86‐0.89 from 1 to <5 years) but at higher risk thereafter (HR, 1.32; 95% CI, 1.27‐1.37 from 5 to 10 years), independent of tumor characteristics and cancer treatment. Similar pattern was found for overall mortality, although the survival benefit was restricted to the first year after diagnosis. Patients diagnosed with lung‐2 face a favorable lung cancer‐specific survival within the early period after diagnosis. A conservative approach to manage lung‐2 solely based on malignancy history is not supported.